(untitled) (Medical Forum Monthly, 2020)
Objective: The objective of this study was to determine the frequency of early complications in mesh repair of paraumbilical hernia. Study Design: Descriptive case series study. Place and Duration of Study: This study was conducted at the Combined Military Hospital, Muzaffarabad from January 2019 to December 2019. Materials and Methods: This study involved 170 patients of both genders aged between 20-50 years undergoing mesh repair of paraumbilical hernia. These patients were followed in the post-operative period to look for early complications; wound infection, seroma and hematoma formation. A written informed consent was taken from every patient. Statistical analysis has been done by SPSS 20.0. Mean±SD has been calculated for age and BMI while frequency and percentage has been calculated for gender, wound infection, seroma and hematoma formation. Data has been stratified for age, gender and BMI to address effect modifiers. Post-stratification chi-square test has been applied taking p-value ≤0.05 as statistically significant. Results: The age of the patients ranged from 20 years to 50 years with a mean of 42.1±6.9 years. Majority (n=147, 86.5%) of the patients were aged between 36-50 years. There were 34 (20.0%) male and 136 (80.0%) female patients with a male to female ratio of 1:4. BMI of these patients ranged from 24.0 Kg/m2 to 34.8 Kg/m2 with a mean of 30.3±2.8 Kg/m2. Among the various complications, wound infection was the most frequent and was observed in 15 (8.8%) patients followed by seroma (n=12, 7.1%) and hematoma (n=6, 3.5%) formation. When stratified, there was no significant difference in the frequency of wound infection, seroma and hematoma formation across various subgroups based on patient’s age, gender and BMI. Conclusion: Wound infection and seroma formation were observed in a substantial proportion of patients undergoing mesh repair of paraumbilical hernia which warrant meticulous surgical dissection and appropriate antibiotic prophylaxis in such patients to decrease the likelihood of these complications as well as watchful follow-up to timely identify and treat these complications when they occur.